AB0710 Causes and Risk Factors for Death in Systemic Sclerosis – Experience of a Eustar Center. (9th June 2015) - Groseanu, L.; Gudu, T.; Predeteanu, D.; Balanescu, A.; Bojinca, V.; Saulescu, I.; Opris, D.; Borangiu, A.; Constantinescu, C.; Negru, M.-M.; Berghea, F.; Abobului, M.; et al.
Abstract : Background: Systemic sclerosis (SSc) has a case-based mortality that is one of the highest among the rheumatic diseases. Objectives: To identity predictors of mortality in patients with systemic sclerosis from their first evaluation in a reference center Methods: 90 SSc patients were followed between JAN 2010 – JAN 2015. A complete baseline evaluation of all patients was done according to MEDS evaluation sheets (demographics, disease history, main organ involvement). A complete follow-up was done every year. Univariate and multivariate predictors of survival were assessed using proportional hazards regression modelling Results: Amongst the cohort of 90 patients the mean age at diagnosis was 55, 65 (SD 12, 45) years, medium disease duration was 11, 7 (SD 6, 9) years. Medium disease activity score was 3, 43 (SD 2, 14) years. In the deceased group (10 patients), the mean age of death was 43, 7 years (SD 8, 9 years). The 5- year survival rate at was 88, 88%. The most common cause of SSc-related mortality was pulmonary complications (60%). 70% of deaths were attributed directly to SSc. Of the SSc-related deaths, 28, 57% were attributed to pulmonary fibrosis, 57, 14% to pulmonary arterial hypertension (PAH) and 14, 28% to cardiac causes (arrhythmias). Among the non-SSc-related causes, infections (33%) and malignancies (33%) were followed by indidental causes (33%). Sex- and age-adjusted univariate analysis identified the diffuse subset, a modified Rodnan score (mRSS)>14, pulmonary fibrosis, pulmonary hypertension, scleroderma renal crisis and a Medsger score>10 to be associated with increased mortality in all patients. Sex- and age-adjusted multivariate model identified a mRSS >14 OR 1, 562 [1.00; 2.42] and pulmonary hypertension OR 1.336 [1.03; 1.73] as predictors of death. Conclusions: Disease-related causes, in particular pulmonary hypertension and pulmonary fibrosis accounted for the majority of deaths in SSc. Mortality rate in the center seems to be a little bit higher than the EUSTAR cohort, especially in patients with pulmonary hypertension possibly related to difficult acces to specific vasodilator treatment. Higher Rodnan skin scores at baseline evaluation still remains an important mortality predictor. References: Nikpour M, Baron M. Mortality in systemic sclerosis: lessons learned from population-based and observational cohort studies. Curr Opin Rheumatol. 2014;26(2):131-7 Tyndall AJ, Bannert B, Vonk M, Airò P, Cozzi F, Carreira PE et al. Causes and risk factors for death in systemic sclerosis: a study from the EULAR Scleroderma Trials and Research (EUSTAR) database.Ann Rheum Dis. 2010 Oct;69(10):1809-1 Disclosure of Interest: None declared